2019
DOI: 10.3389/fncel.2019.00552
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Motor Deficit and Diffuse Cortical Atrophy Following Focal Cortical Ischemia in Athymic Rats

Abstract: Development of new stroke therapies requires animal models that recapitulate the pathophysiological and functional consequences of ischemic brain damage over timeframes relevant to the therapeutic intervention. This is particularly relevant for the rapidly developing area of stem cell therapies, where functional replacement of circuitry will require maturation of transplanted human cells over months. An additional challenge is the establishment of models of ischemia with stable behavioral phenotypes in chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 36 publications
3
9
0
Order By: Relevance
“…The widespread loss of striatal neurons following injection of ET-1 into the adult forebrain is consistent with the pattern of ischemic damage we (Ermine et al, 2019;Somaa et al, 2017) and others (Gilmour et al, 2004) have previously reported and shown to be associated with a deficit in motor function that is stable over months. The robust proliferative response to injury, shown as a significant increase in BrdU+ cells relative to saline-treated controls, is a well-described response to acute brain injuries (Cavanagh, 1970;Nait-Oumesmar et al, 1999;Wright et al, 2016) including those arising from ischemic damage (Arvidsson et al, 2002;Liu et al, 2009;Parent et al, 2002).…”
Section: Discussionsupporting
confidence: 89%
“…The widespread loss of striatal neurons following injection of ET-1 into the adult forebrain is consistent with the pattern of ischemic damage we (Ermine et al, 2019;Somaa et al, 2017) and others (Gilmour et al, 2004) have previously reported and shown to be associated with a deficit in motor function that is stable over months. The robust proliferative response to injury, shown as a significant increase in BrdU+ cells relative to saline-treated controls, is a well-described response to acute brain injuries (Cavanagh, 1970;Nait-Oumesmar et al, 1999;Wright et al, 2016) including those arising from ischemic damage (Arvidsson et al, 2002;Liu et al, 2009;Parent et al, 2002).…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, this is commonly observed in HI models, where atrophy occurs ipsilateral to the ligation site [ 26 , 27 , 29 ]. Quantification of neuronal density showed that the atrophy was indeed associated with neuronal loss, as opposed to collapse of the extra-cellular compartment as we have reported previously for both neonatal [ 17 ] and adult [ 41 ] models of ET-1 induced ischemic injury in rats. We also observed significant atrophy of white matter structures including the CC and PVWMBs in the dorso-medial striatum; comparable to human clinical data [ 1 , 6 , 25 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Discussionsupporting
confidence: 75%
“…Animals under deep anesthesia (2% isoflurane) were placed in a stereotaxic frame, and focal ischemic injury was induced by injection of the vasoconstrictor, ET-1 (800 pmol in saline; AusPep), into the sensorimotor cortex at two sites (0.5 and 2.0 mm rostral and 2.8 mm lateral to the bregma and 1.5 mm below the surface of the brain) as previously described (Ermine et al, 2019). Control animals received the same volume of saline injected at the same coordinates.…”
Section: Surgical Procedures and Study Designmentioning
confidence: 99%
“…A first cohort of animals was used for histological analysis at 1, 4, 12, 24, 36, and 48 weeks postsurgery (n = 6 allocated per group for each time point, based on our previous work using this model (Ermine et al, 2019)). Two rats died during the surgical procedure and two others spontaneously developed tumor growth during the course of the experiment leading to immediate euthanasia.…”
Section: Surgical Procedures and Study Designmentioning
confidence: 99%
See 1 more Smart Citation